STABILITY OF THE TOURISM INDUSTRY: METHODOLOGICAL ASPECTS - A. Sh. Gizyatova (Финансы: теория и практика, 2017)
The purpose of the paper is to justify strategic measures intended to boost the efficiency and ensure the sustainability of the tourism industry through the stability of its operators and well-coordinated work of individual components of the tourism system. The theoretical basis for the research were the works of Russian economists related to the issue in question and expert opinions. The empirical basis of the study were regulations, official data of the RF Federal State Statistics Service (Rosstat), Federal Agency for Tourism, the Russian business practice, the statistical database of the World Tourism Organization (UNWTO). The general research methods used by the author included analysis, synthesis, comparison, hermeneutics, phenomenology, expert assessment. The key quantitative parameters and definitions are proposed making it possible to give qualitative characteristics of the tourism system; a semantic analysis of the concepts of “reliability”, “sustainability”, “financial stability” of travel companies, particularly, in the field of foreign tourism was made allowing a multi-pronged approach to their use. Based on expert assessments, direct and indirect reliability criteria for travel companies were formulated and listed. The block diagram of a comprehensive economic analysis of travel companies focused on the development of adequate methodological tools to assess their key performance indices was developed.